A study on the distribution of BK and JC polyomavirus in discarded donor kidneys - Moest, Wouter T.; de Vries, Aiko P. J.; Lalai, Reshma A.; Baelde, Hans J.; Kers, Jesper; Wessels, Els; Doppenberg, Jason B.; Engelse, Marten A.; Feltkamp, Mariet C. W.; Rotmans, Joris I. (Frontiers in Transplantation, 2025)
IntroductionBK polyomavirus (BKPyV) and JC polyomavirus (JCPyV) are thought to establish persistent, low-grade infections in the kidney. However, their specific intrarenal reservoirs remain unclear. To explore their localization and potential presence prior to transplantation, we analyzed different kidney regions from deceased donors.MethodDonor kidneys discarded for donation and subsequently designated for research purposes between November 2023 and October 2024 were included. For each kidney, cortex, medulla, pelvis, and ureter were sampled. These samples were analyzed using qPCR for the presence of JCPyV and BKPyV.ResultsIn total, 10 kidneys were analyzed with a total 72 samples taken from the cortex: n = 22, medulla: n = 22, renal pelvis: n = 14, and ureter: n = 14. All samples tested negative for BKPyV. JCPyV DNA was detected in 4 out of 10 kidneys. When analyzed by tissue type, positive samples were found in 6/22(27.3%) cortex, 6/22(27.3%) medulla, 4/14(28.6%) renal pelvis, and 4/14(28.6%) ureter samples. The cycle threshold (Ct) values did not show significant differences among the various regions within the kidney. Notably, JCPyV distribution within individual kidneys was markedly heterogeneous, with substantial variation in Ct-values within the same kidney.ConclusionJCPyV DNA was detected in 40% of kidneys from deceased donors, with comparable detection rates across cortex, medulla, pelvis, and ureter, suggesting no clear tissue preference. However, within individual kidneys, the distribution and Ct-values varied considerably. BKPyV DNA was not detected in any sample. These findings support the hypothesis that JCPyV may be present prior to transplantation and potentially donor-derived. The potential role of JCPyV in kidney transplant recipients and its relationship with BKPyV warrant further investigation.